Purificação de IgG do soro humano utilizando matrizes de hidroxiapatita de estrôncio e de quitosana-alginato com corantes imobilizados - Laurentino, Larissa da Silva (2022)
Human immunoglobulins, especially IgG, are antibodies with wide therapeutic application in the treatment of diseases of the immune system, which justifies their need for high purity, normally achieved with chromatographic methods. This work aimed to evaluate the potential of chitosan-alginate microcomposite matrices with immobilized reactive dyes and strontium hydroxyapatite nanoparticles (SrHAp) in a chromatographic process aiming at the purification of human IgG. Four chitosan-alginate (MQA) microcomposites were obtained with immobilized reactive dyes: MQA-Cibacron Blue F3GA (MQA-CB), MQA-Reactive Blue 4 (MQA-RB), MQA-Reactive Red 120 (MQA-RR) and MQA- Procion Red MX5B (MQA-PR). The materials were characterized by Fourier Transform Infrared Spectroscopy (FTIR), Thermogravimetric Analysis (TGA) and Differential Scanning Calorimetry (DSC). SrHAp nanoparticles were synthesized via co-precipitation and subjected to heat treatment for 5h. Fundamental batch data (effect of pH, kinetics and adsorption isotherm) were obtained using solutions with IgG, in addition to solutions with a mixture of IgG and human serum albumin (HSA). The incorporation of the dyes under study significantly increased the adsorption of IgG, showing an adsorption of 625.28 mg/g for MQA-CB, 1022.17 mg/g for MQA-RB, 698.38 and 718.57 mg/g for the MQA-PR and MQA-RR, respectively. In the chromatographic assays, according to the SDS-PAGE electrophoresis analyses, a purification of IgG with the MQA-RR matrix was achieved. In contrast, the other materials were not able to purify human IgG, being better recommended for a pre-purification of this protein. With regard to SrHaP, it showed a high adsorption capacity (1128.63 mg/g). And, through SDS-PAGE electrophoresis analysis, they proved that IgG was the one with the highest retention in the matrix with binary mixtures and diluted human serum.